Investigating the Effect of Public Trust on Tax Compliance - Haning, Mohamad Thahir; Hamzah, Hasniati; Tahili, Mashuri H (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2019)
Upright now, we rarely find any research that measures the effect of the slippery slope framework on taxpayers’ trust in paying their tax. This article seeks to investigate the effect of power and trust as exogenous variables based on the slippery slope frameworks theory while the endogenous one is a public trust of taxpayers. We employ a survey to investigate this matter and conduct quantitative analysis afterward. Respondents are employees at the Tax Service Authorities in three areas, they are, South Makassar, Maros, and Palopo, which are selected by using purposive sampling with a total population of 2,500 people. We use the determination of research sampling 20% of the population leading to a total number of samples of 500 people. The data were gained through questionnaires and analyzed by using SPSS and Structural Equation Modelling (SEM). Our findings indicate that power has a positive and significant effect on the public trust of taxpayers. We also find that trust has a positive and significant effect on the public trust of taxpayers. Moreover, both power and trust have a positive and significant effect on the public trust of taxpayers simultaneously. In this article, we argue that the strategy to increase the public trust of taxpayers’ compliance is through power and trust. The article also confirms that the slippery slope framework can be applied to developing taxpayers’ compliance.